Contracts` Performance Measurement in Czech Construction Companies - Trtílek, Petr; Hanák, Tomáš (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Performance measurement of construction contracts belongs to the crucial activities enabling the improvement of processes in a construction company. The main aim of this paper is to evaluate and analyse performance management practices applied by contractors in the Czech construction sector. Original data were collected using a questionnaire survey and quantified through relative frequency of occurrence. These data have been supplemented by interviews with experts in the field in order to assess the importance of the individual criteria and other relevant performance aspects.
Keywords: performance measurement; construction company; criterion; measurement systems; efficiency; pomiar wydajności; firma budowlana; kryteria efektywności; systemy pomiarowe; efektywność